ANALYSIS OF AUDIENCE RECEPTION ON THE CONTENT OF ANIES BASWEDAN LOW CONTEXT COMMUNICATION MESSAGES ON THE 3rd DEBATE PRESIDENTIAL CANDIDATES 2024 - Luthfi Rais Fadhillah; Andys Tiara; Gilang Kumari Putra (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
The advent of the digital era has precipitated a profound metamorphosis in the communication patterns of Indonesian society, particularly through the medium of social media, which has emerged as the predominant conduit for the dissemination of information and the shaping of public opinion. A salient phenomenon pertains to Anies Baswedan's communication style during the third presidential debate in 2024, which adopted a Low Context Culture (LCC) a direct and explicit communication style contrasting with Indonesia's traditional communication culture, which tends to be implicit and polite called High Context Culture (HCC). The objective of this study is to examine how the audience received and interpreted the LCC messages conveyed by Anies Baswedan during the debate. The theoretical framework of this research draws on Edward T. Hall's cultural communication theory, Hofstede's cultural dimensions, and Anthony Giddens' Runaway World theory, which highlights the dynamics of globalization and digital interaction. The research method employed is a constructivist paradigm with a qualitative approach, combining Stuart Hall's reception analysis and Phillip Mayring's qualitative content analysis. The data presented herein was collected through a meticulous examination of textual content and in-depth interviews with active and relevant  audiences. The findings of the research indicate that audience reception is significantly influenced by cultural background. Anies' LCC communication style has been perceived by some audiences as firm and effective, while others have found it offensive and inappropriate with local cultural norms. This study provides strategic recommendations for the development of political communication in the digital age.